Controlling Shareholders' Preference in Business Groups: Evidence from Korea. Issue 4 (15th March 2020) - Kwon, Yonghyun; Han, Seung Hun
ABSTRACT: This study examines the effect of controlling shareholders' preference on the payout policy of Korean firms. Using a sample of 9495 firm-year observations, we find that firms with individual controlling shareholders (family-owned firms) have a lower payout ratio than those with non-individual controlling shareholders. Further, firms with higher family-individual controlling shareholder ownership by individual controlling shareholders are reluctant to pay cash dividends in family business groups. These results are consistent with the conservative payout hypothesis. An additional test indicates that family business groups' group-level payout tendency influences all group-affiliated firms' payout policies. The results suggest that controlling shareholders' preference for cash dividends determines payout policy.